Qandeel-e-Adab qawaid o insha jamaat hashtum - Maqsood, Saeed (Lahore: Asian educational publishers, 2024)
Qandeel-e-Adab is an Urdu textbook designed to enhance students' language skills through a rich collection of stories, poems, and essays. It emphasizes reading comprehension, vocabulary building, and creative expression while fostering an appreciation for Urdu literature and moral values. The book integrates grammar and writing exercises to develop linguistic and analytical abilities.
Keywords: Urdu grammar